Comparative morphology and ontogeny of the thoracolumbar transition in great apes, humans, and fossil hominins. Issue 134 (September 2019) - Nalley, Thierra K.; Scott, Jeremiah E.; Ward, Carol V.; Alemseged, Zeresenay
Abstract: Variation among extant hominoid taxa in the anatomy of the thoracolumbar vertebral transition is well-established and constitutes an important framework for making inferences about posture and locomotion in fossil hominins. However, little is known about the developmental bases of these differences, posing a challenge when interpreting the morphology of juvenile hominins. In this study, we investigated ontogenetic variation in the thoracolumbar transition of juvenile and adult great apes, humans, and fossils attributed to Australopithecus and early Pleistocene Homo erectus . For each vertebra involved in the transition, we quantified functionally relevant aspects of zygapophyseal form: facet curvature in the transverse plane, facet orientation relative to midline, and the shift in these variables across the thoracolumbar transition, from the antepenultimate rib-bearing thoracic to the first lumbar vertebra (L1). Among extant hominids, adult individuals of Pan and Homo exhibit a greater shift in facet morphology across the thoracolumbar transition in comparison to Gorilla and Pongo . This pattern is driven by interspecific differences in the L1 facets, with those of chimpanzees and humans being more curved and more sagittally oriented. Chimpanzees and humans also experience more change in facet morphology during development relative to gorillas and orangutans. Humans differ from chimpanzees in achieving their adultlike configuration much earlier in development. The fossil specimens indicate that early hominins had adult morphologies that were similar to those of extant Homo and Pan, and that they achieved their adult morphologies early in development, like extant humans. Although it is unclear why adult chimpanzees and hominins share an adult morphology, we speculate that the early acquisition of adultlike L1 zygapophyseal morphology in hominins is an evolutionary novelty related to conferring stability to a relatively long lumbar spine as young individuals are learning to walk bipedally.